PERAMALAN PERMINTAAN RAINCOAT PT. XYZ MENGUNAKAN ALGORITMA MONTE CARLO - Putratama, Virdiandry; Sovia Pramudita, Aditiya (PPM Universitas Logistik dan Bisnis Internasional, 2025)
PT XYZ Bandung is a manufacturing company that produces SNI standard raincoats. The problem that arises at this time is that the company (PT XYZ) finds it difficult to determine the supply of raw materials for the manufacture of Raincoats due to fluctuating or uncertain demand. Forecasting this demand is to minimize the mismatch between demand and inventory of Raincoat products. In this study, the Monte Carlo Algorithm was used. This algorithm is a probabilistic algorithm technique for solving problems with sampling and random processes. Demand forecasting uses data for the past 20 months of 2023-2024. Based on the results of the calculation, it is found that the results of calculations based on data for 2023 February and May, each with a demand of 35,744 units with a total demand of 226,251 Units with an accuracy of 99.80%, while in 2024 January, March, April, and June with 41,913 units with a total demand of 351,496 Units with an accuracy of 93.87%. From these results, it can be concluded that the Monte Carlo Algorithm can predict Raincoat demand forecasting at PT.XYZ Bandung.